What do patients expect? Assessing patient-centredness from the patients' perspective: an interview study. Issue 7 (12th July 2021) - Zeh, Stefan; Christalle, Eva; Zill, Jördis M; Härter, Martin; Block, Andreas; Scholl, Isabelle
Abstract : Objective: Although there has been much conceptual work on patient-centredness (PC), patients' perspectives on PC were neglected. In a previous study, participating patients rated the relevance of 16 dimensions of an integrative model of PC as high to very high. However, it remained unclear which specific behaviours described in the dimensions were considered most relevant. Thus, the aim of the current study was to further explore which of the specific behaviours described in the model are especially relevant for the high ratings in the previous study. Methods and design: We conducted semistructured interviews with 20 patients with chronic diseases (16 females, 4 males, mean age: 52 years). Patients answered questions regarding their experiences in the German healthcare system and how optimal healthcare would look like from their perspective. Furthermore, patients were asked to reflect on the most important aspects which they had mentioned in the interview before. Data were analysed via content analysis. Results: Participants addressed many different aspects of PC, but mostly focused on three major themes: (1) time appropriate access to care, (2) competence, empathy and being taken seriously by HCPs, (3) HCPs' individual consideration of each patient's situation (eg, wishes and needs). Minor themes were: (1) taking a holistic perspective of the patient, (2) patient-centred communication, (3) integration of multidisciplinary treatment elements, (4) transparency regarding waiting time and (5) reduction of unequal access to care. Conclusion: This study enriches the construct of PC by depicting essential aspects of PC from the patients' perspective. The results allow prioritising strategies to implement patient-centred care. Thus, this study helps to pursue the ultimate goal of fostering patient-centred healthcare delivery in Germany.